My browser is not a billboard: Experimental evidence on ad-blocking adoption and users' acquisition of information - Niklas Fourberg; Serpil Taş; Lukas Wiewiorra (WIK Wissenschaftliches Institut für Infrastruktur und Kommunikationsdienste, 2021)
Ad-avoidance technologies such as ad-blocking add-ons in browsers and supplemental mobile applications have become mainstream tools in recent years. Over time they surpassed their niche role as applications only for the technically savvy and became an essential tool for many internet users. While the technical impact of these tools has been well researched, their effects on actual consumer behavior is still unclear. In an experimental setting this study provides first evidence on the effect of ad-blocking on users' ability to acquire information in the form of an online reading task. We find that ad-blocking leads to more effort being exerted and increases social welfare by reducing inefficient searching. Additionally, ad-blocking induces users' visit duration on websites to be more elastic in the experienced intensity of advertisement. Hence, gains in user visit duration from reducing the ad-load are larger, which consequences a more competitive environment among publishers. The results provide new perspectives on ad-blocking and inform the current debate on looming ad-tech regulations in the light of DMA and DSA initiatives.
Keywords: L82; L86; M37; C91; 650; ad-blocking; consumer behavior; lab experiment; online advertising; welfare; privacy